Study on DGAT1 Gene Polymorphism in Surti and Banni Buffaloes By PCR-RFLP - Kharadi, VB; Ramani, UV; Pandya, GP; Dangar, NS; Pawar, VD (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This investigation was undertaken with the objective to study DGAT1 gene exon 8 polymorphism using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) in 53 Surti and 56 Banni buffaloes. The restriction digestion of 412 bp product with AluI revealed only one genotype AA in both Surti and Banni buffaloes. The frequencies of allele A were observed as 0.55 and 0.54 in Surti and Banni buffaloes, respectively on restriction digestion with HincII. The restriction digestion of amplified product with HphI revealed two fragments. The frequency of allele A were 0.71 and 0.36 in Surti and Banni buffaloes, respectively. We found that the 412 bp DGAT1 gene fragment was fairly polymorphic with HincII and HphI restriction enzymes, while monomorphic with AluI restriction enzyme in both buffalo populations studied.
Keywords: Banni; DGAT1; PCR-RFLP; polymorphism; Surti